Survey of Supplement Use and Effects Felt by Amateur Boxers - Trisnar Adi Prabowo; Nevitaningrum; Moch. Septian Resi Wibowo; Wahyu Dwi Yulianto (Indonesian Journal of Physical Education and Sport Science)
Study purpose. To investigate type of supplement and amount of supplement used as well as the perceived effect and needs of boxers.